Antioxidants Hydroxytyrosol and Thioredoxin-Mimetic Peptide CB3 Protect Irradiated Normal Tissue Cells - Katrin Borrmann; Fabian Martin Troschel; Kathrin Annemarie Brücksken; Nancy Adriana Espinoza-Sánchez; Maryam Rezaei; Kai Moritz Eder; Björn Kemper; Hans Theodor Eich; Burkhard Greve (MDPI AG, 2024)
Reducing side effects in non-cancerous tissue is a key aim of modern radiotherapy. Here, we assessed whether the use of the antioxidants hydroxytyrosol (HT) and thioredoxin-mimetic peptide CB3 (TMP) attenuated radiation-induced normal tissue toxicity in vitro. We used primary human umbilical vein endothelial cells (HUVECs) and human epidermal keratinocytes (HaCaT) as normal tissue models. Cells were treated with HT and TMP 24 h or immediately prior to irradiation. Reactive oxygen species (ROS) were assessed via luminescent- and fluorescence-based assays, migration was investigated using digital holographic microscopy, and clonogenic survival was quantified by colony formation assays. Angiogenesis and wound healing were evaluated via time-dependent microscopy. Secreted cytokines were validated in quantitative polymerase chain reaction (qPCR) studies. Treatment with HT or TMP was well tolerated by cells. The application of either antioxidant before irradiation resulted in reduced ROS formation and a distinct decrease in cytokines compared to similarly irradiated, but otherwise untreated, controls. Antioxidant treatment also increased post-radiogenic migration and angiogenesis while accelerating wound healing. HT or TMP treatment immediately before radiotherapy increased clonogenic survival after radiotherapy, while treatment 24 h before radiotherapy enhanced baseline proliferation. Both antioxidants may decrease radiation-induced normal tissue toxicity and deserve further pre-clinical investigation.